2021
DOI: 10.3390/su13052770
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Suitable Potato Genotypes for Late-Sown Heat Stress Conditions Based on Field Performance and Stress Tolerance Indices

Abstract: International Potato Center (CIP), -bred potato genotypes produce various yields under heat stress conditions due to being sown late. To explore options for achieving this, a replicated experiment was conducted at the field of Tuber Crops Research Sub-Centre, Bangladesh Agricultural Research Institute, Bogura, Bangladesh to evaluate the performance of fourteen CIP-bred potato genotypes with two controls (Asterix and Granola). The experiment was laid out in a split-plot design with three replications. Several i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Elevated temperatures during tuber formation decreased the number of tubers per plant ( Zhang et al., 2021 ), and in extreme cases, tuber initiation is inhibited. Additionally, heat stress may delay tuber initiation, resulting in the formation of numerous smaller tubers instead of larger ones ( Mahmud et al., 2021 ), as we found in our experiments. Dalhart produced a higher number of large tubers than Springlake.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Elevated temperatures during tuber formation decreased the number of tubers per plant ( Zhang et al., 2021 ), and in extreme cases, tuber initiation is inhibited. Additionally, heat stress may delay tuber initiation, resulting in the formation of numerous smaller tubers instead of larger ones ( Mahmud et al., 2021 ), as we found in our experiments. Dalhart produced a higher number of large tubers than Springlake.…”
Section: Discussionsupporting
confidence: 56%
“…Environment, cultivar, and their interaction jointly dictate yield capacity ( Benavides-Cardona et al., 2022 ), with environment notably impacting traits like yield and tuber dry matter. A yield reduction of 13% in Brazil ( Patino-Torres et al., 2021 ) was recorded, while in Bangladesh, reductions ranged from 4.5% to 34.8% ( Mahmud et al., 2021 ) due to heat stress. The yield in the current study was higher in field and greenhouse experiments exposed to less heat stress, consistent with findings from previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…(2015), and Al‐Muhmud et al. (2021), different indices lead to divergent ranking in drought tolerance. Zerihun et al (2019) consequently used multiple stress tolerance indices under fully watered non‐stress and terminal drought (irrigation water supply withheld after 50% flowering to induce post‐flowering stress conditions) to identify suitable drought‐tolerance genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…Fernandes Filho et al [ 39 ] have reported a maximum temperature around 30 °C as heat-stress environment for screening potatoes for heat stress. Al Mahmud et al [ 40 ] found that temperatures reaching around 25 °C before the harvest resulted in heat stress on potatoes. A threshold temperature of 25 °C was used to assess the impact of heat stress on potatoes which defined a hot spell as two or more consecutive days with maximum temperatures at or above the threshold [ 41 ].…”
Section: Discussionmentioning
confidence: 99%